2007
DOI: 10.1002/pbc.20911
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with TEL‐AML1‐positive acute lymphoblastic leukemia with single or multiple fusions

Abstract: Utilizing FISH to distinguish subgroups of TEL-AML1 fusion patients may have important prognostic implications. The presence of an extra fusion may portend poorer prognosis. A larger and longer-term follow-up study will be required to verify the possible clinical significance of the presence of multiple TEL-AML1 fusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…6 showed a unique FISH profile where two fusion signals of the ETV6/RUNX1 were detected. Double ETV6/RUNX1 fusion signals were found in 25% of ETV6/RUNX1 positive ALL patients [20]. Previous studies have found that the additional ETV6/RUNX1 fusion signal may have arisen from duplication of the der(21)t(12;21) chromosome [21,22], duplication of ETV6/RUNX1 fusion gene that was later translocated onto another chromosome [22] or ider(21)(q10)t(12;21)(p12;q22) [23].…”
Section: Discussionmentioning
confidence: 99%
“…6 showed a unique FISH profile where two fusion signals of the ETV6/RUNX1 were detected. Double ETV6/RUNX1 fusion signals were found in 25% of ETV6/RUNX1 positive ALL patients [20]. Previous studies have found that the additional ETV6/RUNX1 fusion signal may have arisen from duplication of the der(21)t(12;21) chromosome [21,22], duplication of ETV6/RUNX1 fusion gene that was later translocated onto another chromosome [22] or ider(21)(q10)t(12;21)(p12;q22) [23].…”
Section: Discussionmentioning
confidence: 99%
“…19,24 Expression of CD13 occurs more often than CD33. 24 In our study, both CD13 and CD33 were more frequently expressed in the double ETV6-RUNX1 fusion group than the single-fusion group (Table 3) and were either absent or infrequently expressed in B-ALL with RUNX1 amplification.…”
Section: Discussionmentioning
confidence: 99%
“…24 In our study, both CD13 and CD33 were more frequently expressed in the double ETV6-RUNX1 fusion group than the single-fusion group (Table 3) and were either absent or infrequently expressed in B-ALL with RUNX1 amplification. 1,19 This suggests that the breakpoint of RUNX1 at 21q22 is myeloid associated when fused with other genes, as seen in AML with t(8;21)(q22;q22)/ RUNX1-RUNX1T1 or MDS with t(3;21)(q26;q22)/RUNX1-MECOM. [5][6][7] It also seems that the increased number of ETV6-RUNX1 fusions, rather than gain of the wild-type RUNX1, promotes more frequent expression of myeloidassociated antigens in malignant B-lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently observed translocations in the childhood ALL are t(12;21)(p13;q22) at a rate of 20-25 %; t(9;22)(q34;q11) at a rate of 2 %; and MLL gene rearrangement at a rate of 2-4 % (1, 2). It is stated that in these translocations t(12;21)(p13;q22) is related to good prognosis while t(9;22) (q34;q11) and MLL gene rearrangement are related to poor prognosis (10,11). Except these classic translocations, there are some rare translocations, which might affect prognosis in literature (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%